2017
DOI: 10.1371/journal.pone.0174087
|View full text |Cite
|
Sign up to set email alerts
|

Is the number of siblings associated with dietary patterns in adolescents? The 1993 birth cohort of Pelotas (Brazil)

Abstract: Our study aimed to estimate the association between number of siblings and dietary patterns in adolescents. Prospective longitudinal study was developed using data from the birth cohort of the city of Pelotas, Brazil, which included 5249 participants. At the 18-year-old follow-up, from 4563 individuals located, 4106 were interviewed (follow-up rate 81.3%). Of these, 3751 were included in our principal component analysis of dietary patterns. Regular dietary intake of 45 food groups over the previous year was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…A Spanish study showed that having more than one sibling is associated with a higher nutritional risk [ 28 ]. In the research of Cook et al, cited by [ 29 ], persons having siblings showed lower consumption of all nutrients, with the exception of carbohydrates and added sugar, which was confirmed by our results. One possible explanation is that more siblings means that the family has less to spend on each family member [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A Spanish study showed that having more than one sibling is associated with a higher nutritional risk [ 28 ]. In the research of Cook et al, cited by [ 29 ], persons having siblings showed lower consumption of all nutrients, with the exception of carbohydrates and added sugar, which was confirmed by our results. One possible explanation is that more siblings means that the family has less to spend on each family member [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Having siblings was strongly associated with higher adherence (by 97–98%) to the Inconsequent pattern, characterized by less frequent attempts to limit the consumption of sweets, sugar, and salt. The number and profile of siblings may be related to compliance with specific nutritional patterns or health-related markers, both positive and negative [ 29 , 30 ]. A Spanish study showed that having more than one sibling is associated with a higher nutritional risk [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the research assistants involved in the protocol received training specific to the study, and all steps were undertaken using standard protocols (e.g., revision of all 24HR, double data entry, use of standardised food composition to estimate nutrients in both dietary methods) to minimise errors. This FFQ was applied to identify dietary patterns in previous cohort follow-ups when participants were 15 and 18 years of age, and the FFQ provided relevant findings on dietary patterns that were associated with body composition (30) , number of siblings (31) and blood lipids (32) .…”
Section: Discussionmentioning
confidence: 99%
“…In the last five years, it has been witnessed a trend in the use of methodologies for assessing food consumption in Brazilian children and adolescents based on the identification of dietary patterns 11,12,13,14,15,16,17,18,19,20,1,21,22 . However, such studies involve localized samples, denoting a gap in studies with nationally representative probabilistic samples of Brazilian adolescents according to geographic region.…”
Section: Introductionmentioning
confidence: 99%